High HIV incidence in men who have sex with men attending for postexposure prophylaxis: a service evaluation. (13th July 2016) - Whitlock, G; McCormack, C; Fearnley, J; McOwan, A
Abstract : Background/aims: There are limited outcome data for men who have sex with men (MSM) who have received HIV postexposure prophylaxis (PEP). The objective of this service evaluation was to determine HIV incidence and repeat PEP use among MSM PEP recipients in London, UK. Methods: Retrospective electronic case-note review of all MSM who were prescribed PEP between January and April 2013 at a central London sexual health service. Results: 530 MSM received PEP between 1 January and 30 June 2013. Of these, 449 had more than 30 days subsequent follow-up at our service. Median age was 31 years. PEP indication was unprotected anal intercourse, 98% (receptive 88% and insertive 10%) and other, 2%. Up to 1 November 2015, total follow-up was 756 person-years. 183 users received repeat PEP. The total number of repeat PEP courses was 442. 57 MSM newly acquired HIV: the HIV incidence was 7.6 per 100 person-years. Conclusions: PEP was associated with a high risk of subsequent HIV seroconversion in this cohort; this group may be appropriate candidates for pre-exposure prophylaxis.